Macro and micropolitics recontextualization of an integrated curriculum: experienced itinerary in nursing undergraduate - Elaine Cristina Dias Franco; Amanda Nathale Soares; Maria Flávia Gazzinelli (Escola Anna Nery, 2018)
Abstract Aim: To analyze the process of recontextualization of an integrated curriculum of Nursing Undergraduate Program. Method: Qualitative research, of a single case study, developed through documentary analysis, systematic observation and a semi-structured interview with nine teachers. Analysis of data by Critical Discourse Analysis. Results: The process of recontextualizing an integrated curriculum in the contexts of the Policy Cycle reveals that, in the Context of Influence and Textual Production, the curriculum is the result of a bricolage of educational policies, health policies and experiences of other institutions. Conclusion: Fragilities related to the organization of the modular structure and the teacher's close approximation to the Textual Production Context of the curriculum, associated to the training experience, favor the recontextualization of the curricular proposal when it is translated into the Context of Practice. It is necessary to institute strategies that integrate teacher education into their daily lives in curricular policies.